Nutritional status of exclusive compared to non exclusive breastfeeding mother - Pangestuti, Dina Rahayuning (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This study aimed to compare the nutritional status of exclusive and non-exclusive breastfeeding mothers with cross-sectional study design. Study location was Gayamsari public health center working area, Semarang city, Central Java Province, Indonesia. Sixteen exclusive breastfeeding mothers and 16 non exclusive breastfeeding mothers were recruited. Mothers with infant aged 4 months were assessed for their anthropometry (weight, height, mid-upper-arm-circumference, and body fat percentage), dietary intakes (24 hours recall in week day and week end) and hemoglobin level. Nutrition fulfillment of dietary intake was calculated based on Indonesia RDA according to age group. Univariate analysis was used to calculate the frequency, independent T-test and Mann-Whitney test were used to analyze differences in assessment results between groups. The results showed that mean aged of subject was 28.3±5.4 years, median parity was 2 childrens, mean BMI was 23.0±4.2 kg/m2. In total, 12.5%, 40.6%, and 46.9% of the subjects were classified as underweight, normal, and overweight respectively. There is no significant difference (p>0.05) in nutritional status between groups. Subjects who fulfill the daily intake recommendation was only 16.1% for protein, 9.7% for fat, 12.9% for vitamin A, 6.5% for vitamin C, 3.2% for folic acid, and 3.2% for calcium. There was no significant difference in daily intake between groups. Mean hemoglobin level of subject was 12.1±1.6 mg/dl. 50% of the subjects were considered as anemic and no significant difference was found between groups (p>0.05). In conclusion, there is no significant difference between exclusive and non-exclusive breastfeeding group in nutritional status, nutrition adequacy and hemoglobin level. Less than half of the subjects were categorized as having a normal nutritional status. None of subject fulfill the daily energy, Fe and Zn requirements.